2018
DOI: 10.1080/10942912.2018.1564761
|View full text |Cite
|
Sign up to set email alerts
|

Lipid characteristics and tocopherol content of the oils of native avocado cultivars grown in Indonesia

Abstract: The oils obtained from three Indonesian avocado (Persea americana) cultivars namely Merah bundar, Ijo bundar and Ijo panjang, were compared to the oils obtained from imported Fuerte and Shepard avocado varieties in terms of lipid characteristics and tocopherol content. The oils of all avocado varieties existed in a semisolid form, except that of the Fuerte variety. Free fatty acids and peroxide levels in the oils obtained from locally grown avocado were lower than the levels in the oils obtained from imported … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 32 publications
2
20
0
Order By: Relevance
“…Another factor with a significant influence on the content of tocopherols in avocado oil is the avocado fruit variety. Manaf et al (2018) observed that avocado oil extracted from fruit of Indonesian varieties (Merah bundar, Ijo bundar, and Ijo Panjang) had higher tocopherol content (50, 46, and 50 μg/g oil, respectively) compared to commercial varieties (Fuerte = 37 μg/g oil and Shepard = 33 μg/g oil).…”
Section: Tocopherolsmentioning
confidence: 94%
See 1 more Smart Citation
“…Another factor with a significant influence on the content of tocopherols in avocado oil is the avocado fruit variety. Manaf et al (2018) observed that avocado oil extracted from fruit of Indonesian varieties (Merah bundar, Ijo bundar, and Ijo Panjang) had higher tocopherol content (50, 46, and 50 μg/g oil, respectively) compared to commercial varieties (Fuerte = 37 μg/g oil and Shepard = 33 μg/g oil).…”
Section: Tocopherolsmentioning
confidence: 94%
“…Manaf et al. (2018) observed that avocado oil extracted from fruit of Indonesian varieties (Merah bundar, Ijo bundar, and Ijo Panjang) had higher tocopherol content (50, 46, and 50 μg/g oil, respectively) compared to commercial varieties (Fuerte = 37 μg/g oil and Shepard = 33 μg/g oil). The impact of the stage of fruit ripening on the tocopherol content is not very clear.…”
Section: Some Lsbc Present In Avocado Oilmentioning
confidence: 99%
“…Soybean tocopherols were rich in γ-tocopherol (>66 %), whereas δ-tocopherol was >21% and α-tocopherol was 11%. Interestingly, α-tocopherol accounted for 100% of the total tocopherols in avocado oils [50,51].…”
Section: Main Components Of Asumentioning
confidence: 99%
“… Jorge et al. (2016) Avocado ‘Merah bundar’, ‘Ijo bundar’, ‘Ijo panjang’ ‘Merah bundar’ and ‘Ijo bundar’ showed higher γ and α-tocopherols, respectively Manaf et al. (2018) GAE = gallic acid equivalence.…”
Section: Preharvest Factors Affecting Quality Attributes Of Edible Frmentioning
confidence: 99%